Quasi-2D thermal network based heat soakage model for gas turbine transient performance modification - Yang, Yimin; Nikolaidis, Theoklis; Pilidis, Pericles (Elsevier, 2024)
To overcome the limitations of traditional heat soakage analysis, a novel quasi-2D thermal network based heat soakage model is established with the consideration of component internal thermal resistance, combustor temperature profile, cooling technologies and thermal barrier coating. The method has been integrated into Turbomatch, a gas turbine performance software developed by Cranfield University, to offer a more realistic estimation of the heat soakage effect during the gas turbine transient manoeuvre. The accuracy of the heat soakage model has been validated against results obtained from GasTurb. Furthermore, a parametric analysis has been conducted to evaluate the effects of combustor temperature profile, cooling technologies, and thermal barrier coating. It is found that the combustor temperature profile will cause a significant increase in heat flow rate, which is approximately four times the conventional lumped parameter method based model. The implementation of cooling technologies and thermal barrier coating will reduce the heat flow rate by 48.97%. More importantly, the change in heat flow rate causes a further delay in engine transient response. Corrected rotational speed was decreased by 0.89%, and thrust was reduced by 2.24%. Moreover, a delay of 8s (233% increase) in the transient acceleration time was found when comparing the quasi-2D thermal network based heat soakage model with the traditional lumped parameter method based model. These highlight the significance of accurately evaluating the heat soakage effects during gas turbine transient simulation.
Keywords: Gas Turbine Transient; Heat Soakage Effect; Quasi-2D Thermal Network; Performance Simulation; Response Delay